2016
DOI: 10.1371/journal.pone.0164723
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Optimal Insertion Site in Recombinant Newcastle Disease Virus (rNDV) Vector Expressing Foreign Gene to Enhance Its Anti-Tumor Effect

Abstract: Recombinant Newcastle disease virus (rNDV) is tumor selective and intrinsically oncolytic, which has been developed as a vector to express exogenous genes to enhance its oncolytic efficacy. Our previous studies found that insertion sites of foreign gene in rNDV vector affected its expression and anti-tumor activities. However, the optimal insertion site for foreign genes remains unknown. In this study, we inserted the enhanced green fluorescence protein (EGFP) and IL2 genes into four different intergenic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…Finally, marker genes and other inserted sequences in viral vectors may affect the overall fitness of the resulting virus, as shown in a number of cases. 47 , 48 , 49 , 50 , 51 , 52 Therefore, our study has confirmed the great advantages of the SEM system for the removal of marker genes.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, marker genes and other inserted sequences in viral vectors may affect the overall fitness of the resulting virus, as shown in a number of cases. 47 , 48 , 49 , 50 , 51 , 52 Therefore, our study has confirmed the great advantages of the SEM system for the removal of marker genes.…”
Section: Discussionsupporting
confidence: 71%
“…Although NDV is naturally tumor-selective, there are inherent problems with the virus which need to be overcome in order to improve its ability to infect and spread within solid tumors as viral spread is limited by factors such as the extra-cellular matrix ( 95 ). Again, there are many studies looking at ways to modify this virus to make it safer and more efficacious; for example, insertion of the IL-2 gene into the NP/P site has proved effective ( 96 ). Inclusion of IL-2 and/or TRAIL has been shown to increase apoptosis levels in infected cells resulting in the tumor-selective parental virus becoming an even more potent anti-cancer agent ( 97 101 ).…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
“…AdV [108] Neuroblastoma [45], Glioma [43], Prostate [48], Squamous Cell Carcinoma [46,47], Melanoma [108] Infiltration of macrophages, T helper, CTL and NK cells [43,45,47,48] No signs [44,46,47] HSV [30,[43][44][45]47,48] Improved survival [108] and protective against rechallenge [47] VSV [46] IL-2 NDV [52][53][54][55][56] Melanoma [54,55], Hepatoma [52,53], Squamous Cell Carcinoma [51] Infiltration of T helper and CTL [51][52][53][54][55][56] No signs [53,54] HSV [51] Immunity against rechallenge with tumor cells [51][52][53][54]…”
Section: Transgene Virus Tumor Additive Immunologic Effects Toxicitymentioning
confidence: 99%
“…Systemic treatment with IL-2 is associated with major adverse side effects in humans [24]. Therefore, local delivery of IL-2 by OVs has been tested by several research groups [51][52][53][54][55][56]. In these murine studies, reduced tumor growth and increased T cell infiltration of the tumors was reported.…”
Section: Il-2 and Il-15mentioning
confidence: 99%
See 1 more Smart Citation